Enhancement of anti-cholinesterase activity of Zingiber cassumunar essential oil using a microemulsion technique - Okonogi S. (2017)
The aim of the present study was to enhance the cholinesterase inhibitory activity of Zingiber cassumunar (ZC) oil using a microemulsion (ME) technique. Pseudoternary phase diagrams of the oil, water, and surfactant/ co-surfactant mixture were constructed using a water titration method. Effects of co-surfactant, surfactant/co-surfactant ratio, ionic strength, and pH were examined by means of the microemulsion region which existed in the phase diagrams. The inhibition of acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) were tested by Ellman's colorimetric assay. It was found that ZC oil possesses inhibitory activity against not only AChE but also BChE. Formulation of ZC oil as ME revealed that alkyl chain length and number of hydroxyl groups of co-surfactant exhibited a remarkable effect on the pseudoternary phase diagram. Longer alkyl chains and more hydroxyl groups gave smaller regions of MEs. Ionic strength also affected the ME region. However, the phase behavior was hardly influenced by pH. The suitable ZC oil ME was composed of Triton X-114 in combination with propylene glycol. The anticholinesterase activity of this ME was much higher than that of native ZC oil. It exhibited twenty times and twenty five times higher inhibitory activity against AChE and BChE, respectively. ZC oil loaded ME is an attractive formulation for further characterization and an in vivo study in an animal model with Alzheimer's disease.